THE GLOBAL VEGETABLE MARKET - Đorović, Milutin; Milanović, Milan; Stevanović, Simo; Lazić, Verica (Economics of Agriculture, 2007)
The aim of the study was to analyze from the regional and comparative standpoints some major indices of the world market and trade of vegetables, essential in the population diet as the obligatory and irreplaceble groupe of commodities. Special reference was given to trends, i.e. output, dynamics and structure of production, trade and consumption of the products analyzed. In addition, regions, i.e. countries known to be the largest producers but no less importers and exporters of vegetables were determined. Significant differences were registered between regions which may be attributed to a large number of natural, social and economic factors. Both quantitative and qualitative research methods of the market were used in the analysis of the relationship and the level of impact of the factors influencing changes and trends of the incidences investigated.